Characterisation of S. aureus/MRSA CC1153 and review of mobile genetic elements carrying the fusidic acid resistance gene fusC - Stefan Monecke (Nature Portfolio, 2021)
Abstract While many data on molecular epidemiology of MRSA are available for North America, Western Europe and Australia, much less is known on the distribution of MRSA clones elsewhere. Here, we describe a poorly known lineage from the Middle East, CC1153, to which several strains from humans and livestock belong. Isolates were characterised using DNA microarrays and one isolate from the United Arab Emirates was sequenced using Nanopore technology. CC1153 carries agr II and capsule type 5 genes. Enterotoxin genes are rarely present, but PVL is common. Associated spa types include t504, t903 and t13507. PVL-positive CC1153-MSSA were found in Egyptian cattle suffering from mastitis. It was also identified among humans with skin and soft tissue infections in Saudi Arabia, France and Germany. CC1153-MRSA were mainly observed in Arabian Gulf countries. Some isolates presented with a previously unknown SCCmec/SCCfus chimeric element in which a mec B complex was found together with the fusidic acid resistance gene fusC and accompanying genes including ccrA/B-1 recombinase genes. Other isolates carried SCCmec V elements that usually also included fusC. Distribution and emergence of CC1153-MRSA show the necessity of molecular characterization of MRSA that are resistant to fusidic acid. These strains pose a public health threat as they combine resistance to beta-lactams used in hospitals as well as to fusidic acid used in the community. Because of the high prevalence of fusC-positive MRSA in the Middle East, sequences and descriptions of SCC elements harbouring fusC and/or mecA are reviewed. When comparing fusC and its surrounding regions from the CC1153 strain to available published sequences, it became obvious that there are four fusC alleles and five distinct types of fusC gene complexes reminiscent to the mec complexes in SCCmec elements. Likewise, they are associated with different sets of ccrA/B recombinase genes and additional payload that might include entire mec complexes or SCCmec elements.